Correlation Analysis between Residual Pain after Vertebral Augmentation and the Diffusion Distribution of Bone Cement: A Retrospective Cohort Study. (4th January 2023) - Yao, Kang; Chen, Yungang; Wang, Xiaoying; Yao, Qianqian; Cui, Kaiying; Chen, Wenming; Hou, Pengfei; Yu, Ning; Zhang, Zhenyue; Gao, Wenxin; Xue, Haipeng; Hao, Yanke
Abstract : Objective . To explore the influence and potential factors of the bone cement dispersion state on residual pain after vertebral augmentation. Methods . The cases included in this retrospective cohort study were patients treated with vertebral augmentation (VA) for osteoporotic vertebral compression fractures (OVCFs) between July 2018 and June 2021. According to the type of cement diffusion distribution, the patients were divided into a sufficient diffusion group (Group A) and an insufficient diffusion group (Group B). The differences in the baseline data, visual analog scale (VAS), Oswestry disability index score (ODI), injured vertebral height (IVH), and local kyphosis angle (LKA) between the two groups were analyzed. Assessments were performed preoperatively on the 2nd day postoperation and at the last follow-up. The imaging data of injured vertebrae were accurately reconstructed by a GE AW4.7 workstation, and the differences in the vertebral body volume, bone cement volume, and bone cement volume ratio were compared between the groups. Result. After screening, 36 patients were included. (1) The postoperative VAS and ODI scores of the two groups were significantly improved compared with the preoperative scores. (2) On the 2nd day postoperation and the last follow-up, the VAS and ODI scores of Group A were significantly different from those of Group B, and Group A outperformed Group B. (3) The IVH and LKA of the two groups were improved after the operation, and no significant difference was found between the groups. (4) Significant differences were found in the bone cement volume and bone cement volume ratio between the groups, and Group A was larger than Group B. Conclusions. Sufficient bone cement diffusion can reduce residual pain after vertebral augmentation.